Status hidrasi, tingkat kebugaran jasmani dan daya konsentrasi anak sekolah dasar - Sudrajat, Agus; Mexitalia, Maria; Rosidi, Ali (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2019)
Background: The dehydration correlated with physical fitness and the cognition. The cardiorespiratory fitness correlated with brain ability and working performance too. Objectives: The purpose of this study is to assess the correlation of dehydration status and cardiorespiratory fitness with the concentration of primary school children.Methods: Correlational study is done to the students aged 10-12 years old. The dehydration status is measured by urine specific gravity. The cardiorespiratory fitness is measured by harvard step test and digit symbol test is used to measure concentration. The analysis of the data using product moment to bivariate analysis and partial correlation to multivariate analysis.Results: The result showed that the average of subjects have a mild (Usg 1020.20±6.99 g/dl). The average of the subjects have a less cardiorespiratory fitness (31.27±8.00). The results of concentration ability measurement showed about of 35±12.27. The correlation analysis showed a significant correlation between dehydration status with cardiorespiratory fitness( r=-0.29, p=0.04 ), between dehydration status with concentration (r=-0.29, p=0.036) and between cardiorespiratory fitness with concentration (r=0.295, p=0.03). Partial correlation analysis showed the persistence of a significant correlation between dehydration status and cardiorespiratory fitness (p=0.02), between dehydration status and concentration (p=0.02) and between cardiorespiratory fitness and concentration (p=0.002).Conclusion: There is a significant correlation between dehydration status and cardiorespiratory fitness. There is a significant correlation between dehydration status and the concentration. There is a significant correlation between cardiorespiratory fitness and the concentration.